Therapeutic ultrasound effects on interleukin-1 beta stimulated cartilage construct in vitro - Park, Kwideok; Hoffmeister, Brent; Han, Dong Keun; Hasty, Karen (ELSEVIER SCIENCE INC, 2007)
A low-intensity ultrasound (LIUS) was examined for its possible therapeutic effects on degenerative osteoarthritic cartilage. Along with the daily treatment of 5 ng interleukin-1 beta (IL-1 beta) for 5 d, an engineered 3D neocartilage construct was used as an in vitro OA model. Followed by 24 h preincubation with the first dose of IL-1 beta, the constructs were then given ultrasonic stimulation (frequency 1.5 MHz and SATA 30 mW/cm(2)) once a day up to 5 d for the predetermined time. Fresh IL-1 beta was added before the stimulation. The difference in the cell number and viability was insignificant between control (US-/IL+) and LIUS-stimulated groups. As the daily stimulation time was extended, the GAG contents in the constructs themselves significantly increased with 50 min stimulation but those released into the culture medium remained unaffected by LIUS. While the gene expression level of aggrecan was similar between control and LIUS (50 min) group, the ratio of collagen type II to type I was found to be higher in the control. The mRNA level of matrix metalloproteinase (MMP)-1 was substantially downregulated in the stimulated construct and that of MMP-13 was indifferent between control and stimulated one. The endogenous expression of transforming growth factor (TGF)-beta 1 and beta 3 was barely responsive to the LIUS stimulation. From histologic analysis, more intense GAG deposition was clearly identified with the LIUS-stimulated constructs. This study indicates that LIUS may have a significant potential to be a chondroprotective stimulant for osteoarthritic cartilage.
Keywords: LOW-INTENSITY ULTRASOUND; PULSED ULTRASOUND; GENE-EXPRESSION; CHONDROCYTES; OSTEOARTHRITIS; PROLIFERATION; APOPTOSIS